Numerical Analysis on the Bending Performance of Prestressed Superposing-Poured Composite Beams - Jianmin Wang; Chengfeng Zhu; Ziqiang Xiao; Qijun Zhao; Junzhe Liu (Advances in Civil Engineering)
Aiming at the bending performance of the prestressed superposing-poured concrete beam, the numerical simulation on the composite beams poured with the normal weight concrete (NWC) superposed on the fibred ceramsite lightweight aggregate concrete (LWAC) was conducted. Three kinds of prestressing schemes, straight linear prestressing force, curved prestressing force not across the casting interface, and curved prestressing force across the casting interface, were simulated for comparison, and the influence of the casting interval time was also considered. Results indicate that the stiffness of the superposing-poured beam can be effectively strengthened by considered schemes of the prestressing force; in addition, there are certain increases on the ultimate load except imposing the straight linear prestressing force. As the curved prestressing force is imposed across the casting interface, the maximal interlayer slip of the casting interfacial transition zone (C-ITZ) approximately equals to that without the prestressing force. The scalar stiffness degradation (SDEG) of the C-ITZ for the casting interval time being 14 days is obvious because of the weakening on the bonding performance of the C-ITZ. Comparatively, the SDEG variation of the C-ITZ in the model with the curved prestressing force across the casting interface is smoother and smaller on the whole than the other two prestressed schemes for the case of the casting interval time being 14 days.